Pengaruh Pelayanan dan Citra Merek Terhadap Kepuasan Pelanggan Maskapai Penerbangan Citilink - Kaela Andiennita; Nerys Lourensius (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the impact of service quality and brand image on customer satisfaction in Citilink airline. Utilizing a quantitative approach, data was collected through a questionnaire distributed to 200 respondents who have used Citilink services. The analysis results indicate a significant positive relationship between service quality and customer satisfaction, with an average satisfaction score of 4.5 on a 5-point scale. Approximately 85% of respondents rated Citilink staff as responsive, while 30% expressed dissatisfaction with cabin cleanliness. Brand image also contributes to customer satisfaction, as 78% of respondents who perceived the brand image positively reported high satisfaction levels. This research identifies a synergy between service quality and brand image, with 82% of respondents linking high service quality to a strong brand image. These findings emphasize the importance for Citilink to integrate both aspects into its marketing and service development strategies to enhance customer experience and strengthen loyalty. The study is expected to contribute to the development of strategies within the competitive airline industry.